PENGARUH KONSENTRASI DAN LAMA PERENDAMAN EKSTRAK TAUGE (Vigna radiata L.) TERHADAP PERKECAMBAHAN TERUNG (Solanum melongena L.) - Nurmiati Nurmiati; Zulkarnain Gazali (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2019)
This study aims to determine the effect of concentration and soaking time of bean sprout extract on eggplant germination. The research method is an experiment that uses a completely randomized design (CRD) with 2 factors. The first factor is the concentration of bean sprout consisting of 5 levels (0% or control, 10%, 20%, 30%, 40%) and the second factor is the duration of soaking which consists of 3 levels (6 hours, 9 hours and 12 hours ). The data obtained were analyzed using univariate analysis, and if the treatment had a significant effect, further tests were carried out using LSD with a level of 5%. The results showed that the concentration and soaking time affected the eggplant germination by measuring parameters namely hypocotyl length and root length of eggplant plants with significance respectively below 0.05 namely 0.008 and 0.005. Concentration and duration of immersion were most influential on the measurement parameters of hypocotyl length of eggplant plants, namely at a concentration of 30% and soaking time of 12 hours with an average length of 5.67 cm. Concentration and duration of immersion were most influential on the parameters of root length measurements of eggplant plants, namely at a concentration of 20% and 12 hours soaking time with an average length of 4.1 cm. The conclusion from the results of this study is the concentration and soaking time have a significant effect on eggplant germination by measuring parameters namely hypocotyl length and root length of eggplant plants.